1994
DOI: 10.1007/bf00201592
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 14 maternal uniparental disomy in the euploid cell line of a fetus with mosaic 46,XX/47,XX,+14 karyotype

Abstract: We investigated the parental origin of the extra chromosome 14 and of the two chromosomes 14 of the euploid cell line, in a case of fetal mosaicism 46,XX/47,XX+14 diagnosed at amniocentesis. Molecular analysis of five polymorphic loci of the short tandem repeat type was performed. Markers D14S43 and D14S49 showed the presence of maternal uniparental disomy of chromosome 14 in the apparently normal cell line. The distribution of the markers analysed along the chromosome suggests maternal heterodisomy with a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…This has already been shown for UPD 14 [20,21] 5. A potential further candidate for a UPD search would be a child with a multiple congenital anomalies/mental retardation (MCA/MR) syndrome or growth retardation born to an "old" mother, the mechanism being the same as outlined above under 4.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…This has already been shown for UPD 14 [20,21] 5. A potential further candidate for a UPD search would be a child with a multiple congenital anomalies/mental retardation (MCA/MR) syndrome or growth retardation born to an "old" mother, the mechanism being the same as outlined above under 4.…”
Section: Introductionsupporting
confidence: 63%
“…Maternal UPD 15 is a well-established cause of the PWS, accounting for about 30% of the cases; paternal UPD 15 is responsible for the AS in about 1-2% of cases. Maternal UPD 7 leads to intrauterine and postnatal growth retardation with or without the full pattern of the Silver-Russell syndrome (SRS) [25] Segmental (for segment llpl5) or mosaic paternal UPD 15 is the cause of the Beckwith-Wiedemann syndrome (BWS) in about 10% of cases [26,27], Furthermore, there is a suspicion that both paternal and maternal UPD 14 lead to phenotypic abnormalities in the probands although, as mentioned above, hidden mosaicism in these cases is not fully excluded and has been demonstrated in at least one instance [21,28]; the phenotypes of the different UPD 14 cases, both maternal and paternal, do not yet allow definition of a recognizable syndrome. In maternal UPD 16, intrauterine growth retardation is frequent, and occasionally other congenital anomalies, including anal atresia, occur [29].…”
Section: Phenotypes Due To Updmentioning
confidence: 99%
“…In humans, some imprinting anomalies have been reported in both maternal and paternal disomies for chromosome 14q (mUPD14 and pUPD14, respectively) (Ledbetter & Engel 1995;Engel 1997). Patients with pUPD14 show a musculoskeletal problem and mental retardation (Cotter et al 1997;Wang et al 1991;Papenhausen et al 1995;Walter et al 1996), whereas mUPD leads to short stature and precocious puberty (Antonarakis et al 1993;Temple et al 1991;Pentao et al 1992;Healey et al 1994;Sirchia et al 1994;Coviello et al 1996;Robinson & Langlois 1996;Tomkins et al 1996;Splitt & Goodship 1997;Miyoshi et al 1998b;Berends et al 1999;Fokstuen et al 1999;Martin et al 1999;Ralph et al 1999), suggesting that there are some imprinted genes in this region. We have found that the human homologue, MEG3, is an imprinted gene which is preferentially expressed from the maternal allele.…”
Section: Introductionmentioning
confidence: 99%
“…Trisomy rescue may occur in two distinct ways at the first zygotic cleavage by chromatid nondisjunction at metaphase or chromosome lag at anaphase, or at various stages thereafter by the same mechanisms, with the initial zygotic makeup preserved in one stem cell. Figure 2 illustrates how trisomy rescue may operate [8,9,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] by reduction to disomy according to two distinct mechanisms, both of which can generate mosaicism, in theory at least [38][39][40][41][42][43][44][45].…”
Section: Mechanisms Generating Updmentioning
confidence: 99%